2015
DOI: 10.3402/jom.v7.27182
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization of initial acquisition of Streptococcus mutans in American Indian children

Abstract: BackgroundSevere-early childhood caries (S-ECC) is one of the most common infectious diseases in children and is prevalent in lower socio-economic populations. American Indian children suffer from the highest levels of S-ECC in the United States. Members of the mutans streptococci, Streptococcus mutans, in particular, are key etiologic agents in the development of caries. Children typically acquire S. mutans from their mothers and early acquisition is often associated with higher levels of tooth decay.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 51 publications
2
37
0
1
Order By: Relevance
“…1). The diversity of genotypes observed in this study is generally similar to other large-scale studies of S. mutans using AP-PCR (Lynch, Villhauer, Warren, Marshall, Dawson, Blanchette, Phipps, Starr and Drake, 2015, Palmer, Nielsen, Peirano, Nguyen, Vo, Nguyen, Jackson, Finlayson, Sauerwein, Marsh, Edwards, Wilmot, Engle, Peterson, Maier and Machida, 2012). While some studies have reported more amplitypes with AP-PCR from smaller sample pools, it should be noted in all gel based genotyping studies there is a degree of variability due to interpretation, techniques and conditions employed.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…1). The diversity of genotypes observed in this study is generally similar to other large-scale studies of S. mutans using AP-PCR (Lynch, Villhauer, Warren, Marshall, Dawson, Blanchette, Phipps, Starr and Drake, 2015, Palmer, Nielsen, Peirano, Nguyen, Vo, Nguyen, Jackson, Finlayson, Sauerwein, Marsh, Edwards, Wilmot, Engle, Peterson, Maier and Machida, 2012). While some studies have reported more amplitypes with AP-PCR from smaller sample pools, it should be noted in all gel based genotyping studies there is a degree of variability due to interpretation, techniques and conditions employed.…”
Section: Discussionsupporting
confidence: 88%
“…The total number of children was adjusted for comparison with mothers (n=105) since not all children had mothers participating in the study and 1 child was eliminated because no S. mutans were recovered. The number of genotypes in this study was 1 −9 per child whereas others have reported that children harbor between 1–6 genotypes (Alves, Nogueira, Stipp, Pampolini, Moraes, Goncalves, Hofling, Li and Mattos-Graner, 2009, Cheon, Moser, Whiddon, Osgood, Momeni, Ruby, Cutter, Allison and Childers, 2011, Cheon, Moser, Wiener, Whiddon, Momeni, Ruby, Cutter and Childers, 2013, Domejean, Zhan, DenBesten, Stamper, Boyce and Featherstone, 2010, Liu, Zou, Shang and Zhou, 2007, Lynch, Villhauer, Warren, Marshall, Dawson, Blanchette, Phipps, Starr and Drake, 2015, Pieralisi, Rodrigues, Segura, Maciel, Ferreira, Garcia and Poli-Frederico, 2010). The average number of genotypes per child in this study was 2.7 and is notably higher than what others have reported for children (range 1.5–2.0) (Cheon, Moser, Whiddon, Osgood, Momeni, Ruby, Cutter, Allison and Childers, 2011, Cheon, Moser, Wiener, Whiddon, Momeni, Ruby, Cutter and Childers, 2013, Domejean, Zhan, DenBesten, Stamper, Boyce and Featherstone, 2010, Liu, Zou, Shang and Zhou, 2007, Lynch, Villhauer, Warren, Marshall, Dawson, Blanchette, Phipps, Starr and Drake, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Samples were collected and processed as detailed by Lynch et al (2015). Briefly, trained and calibrated dental hygienists collected whole mouth plaque samples from Native American Indian children and their mothers (or primary caregivers) at 8 time points from the child’s birth to age 36 months by swabbing all smooth surfaces of the teeth (oral mucosa and tongues of children prior to tooth eruption).…”
Section: Methodsmentioning
confidence: 99%